An Investigation of EFL Students’ Anxiety towards Online English Learning in Paragraph based Writing Subject - Jaelani Bayu Sagara (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2020)
This study aims to investigate the students’ anxiety related to the online English learning in writing subject as well as the factors that contribute anxiety during online learning, and exploring the students’ anxiety strategies in overcoming their anxiety for this study. One of private university in Cirebon was chosen as the site for this study. This study employed qualitative study with a case study design. Students’ anxiety from fourth semester in academic year 2019/2020 was chosen as the participant of this study. The data were collected through interview and questionnaire. This study discovered that students’ anxiety related to the English online learning is situation-specific anxiety, and the factors that contribute anxiety which can be group into four categories: being not familiar with the situation in, incompetence in learning, less English proficiency, no match with expectation. This study also identifies four category strategies employed by students’ anxiety: positive thinking, keep calm and enjoy it, self-confidence, and preparation. The findings of this study provide experiences for students about anxiety that can arise during online learning in unsupportive situation. Keywords: Anxiety; Types of Anxiety; Online Learning, Writing Skill; Paragraph Based Writing.